Global Value Chains and Developing Country Employment A Literature Review - Shepherd, Ben (OECD Trade Policy Papers, 2013)
This paper provides a review of the available literature on global value chains (GVCs) and employment markets in developing countries. Due to the difficulty of observing intra-GVC transactions, there is very little direct empirical work on GVCs and labour markets. However, it is possible to extrapolate from the extensive empirical work already undertaken on firm internationalisation and labour markets to draw inferences as to the likely impacts of GVCs. The review therefore focuses on the labour market impacts of three processes that lie at the core of GVC development: importing, exporting, and foreign direct investment (FDI). It examines their impact on labour demand and wages, and disaggregates the effects whenever possible by skill level. The available empirical evidence strongly suggests that the type of activities undertaken by GVC participants influence labour market outcomes. For instance, many GVC firms are vectors of technological upgrading that in turn increases the relative demand for skilled labour. In these cases, GVC participation is linked to higher relative wages for skilled workers, but also greater wage inequality between skilled and unskilled workers. The evidence on outcomes is more mixed as regards pure processing trade (assembly), however: the limited data available on firms engaged purely in these activities suggests that they do not systematically pay higher wages than domestic firms, which is the reverse of the finding for foreign-owned firms, exporters, and importers in general. The labour market effects of GVCs in developing countries are therefore likely to be broadly positive, but highly case specific. The review therefore concludes with two case studies-electronics in Asia and services in Chile-that demonstrate the complexity of the issues involved, and the role of complementary policies in areas such as human capital development